Syrian Hamster as an Animal Model for the Study on Infectious Diseases - Miao, Jinxin; Chard, Louisa S.; Wang, Zhimin; Wang, Yaohe (Frontiers in Immunology, 2019)
Infectious diseases still remain one of the biggest challenges for human health. In order to gain a better understanding of the pathogenesis of infectious diseases and develop effective diagnostic tools, therapeutic agents and preventive vaccines, a suitable animal model which can represent the characteristics of infectious is required. The Syrian hamster immune responses to infection are similar to humans and as such, this model is advantageous for studying pathogenesis of infection including post bacterial, viral and parasitic pathogens, along with assessing the efficacy and interactions of medications and vaccines for those pathogens. This review summarizes the current status of Syrian hamster models and their use for understanding the underlying mechanisms of infection of pathogens, in addition to their use as a drug discovery platform and provides a strong rationale for the selection of Syrian hamster as animal models in biomedical research. The challenges of using Syrian hamster as an alternative animal model for the research of infectious diseases are also addressed.